(untitled) (Педагогіка вищої та середньої школи, 2007)
The article highlights one of the aspects of developing art education in Ukraine at the end of the 19-th and the beginning of the 20-th centuries. The detailed anafysis of researches publications in this country examines Mirgorod art school and its activities as one of the first educational establishments in the field of art, its curricula, methods of teaching art subjects.